Determination of Potential Drug-Drug Interactions in Patients Using Quinolone Group Antibiotics - Cengizhan Ceylan; Erdenay Erden; Cansu Göncüoğlu; Harun Kızılay; Şeyma Tetik Rama; Yeşim Şerife Bayraktar; Jale Bengi Çelik; Görkem Yılmazer; Esranur Kıratlı; Nazlım Aktuğ Demir; Şua Sümer; Onur Ural (Genel Tıp Dergisi)

(untitled)
Aim: The aim of the study was to determine the potential drug drug interactions of patients receiving inpatient treatment in the intensive care unit and infectious diseases ward and using quinolone group antibiotics by using different interaction software programs.Material and Methods: The prescriptions of 100 patients who received inpatient treatment in infectious diseases service and intensive care unit at Selçuk University Faculty of Medicine Hospital between January 2022 and December 2022 and who were treated with quinolone group antibiotics during treatment were analyzed retrospectively.Results: Of the patients included in the study, 62 were male and 38 were female. The mean age of men was 65.76 ± 16.22 years, while the mean age of women was 68.63 ± 16.29 years. While Medscape® detected a total of 1776 interactions, this number was 1432 in Lexicomp® and 1693 in Drugs®.While 0.33% of the interactions detected in the Medscape® software program were contraindicated, 3.77% of the interactions were contraindicated in Lexicomp®. Kendall W coefficient 0.94, Chi-Square test 281.12, p <0.001 were found to be statistically significant. The software programs used to detect pDDIs are highly compatible with each other. Conclusion: High agreement was found between software programs used to detect potential drug-drug interactions. Interaction classifications between software programs are different. Therefore, clinicians may benefit from different software programs.